Factor momentum, option-implied volatility scaling, and investor sentiment - Grobys, Klaus; Kolari, James W.; Rutanen, Jere (Palgrave Macmillan, 2021)
Factor momentum produces robust average returns that exhibit a similar economic magnitude as stock price momentum. To the extent that the post-earnings announcement drift (PEAD) factor captures mispricing, winner factors earn profits from being long on underpriced stocks and short on overpriced stocks. Conversely, loser-factors’ negative exposure to the PEAD factor suggests that loser factors capture mispricing by being long on overpriced stocks and short on underpriced stocks. Option-implied volatility scaling increases both the economic magnitude and statistical significance of factor momentum. Factor momentum is not exposed to the same crashes as stock price momentum and therefore could provide a hedge for stock price momentum crash risks. Also, factor momentum mispricing is more pronounced when investor sentiment is high.
Keywords: Asset pricing; Factor momentum; Investor sentiment; Option-implied volatility scaling; VIX; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|